Анализа вазоактивних и оксидативних показатеља стреса за процену ефикасности континуираног притиска позитивног дисајног пута и однос вазоактивних и оксидативних показатеља стреса и срчане функције у опструктивним пацијентима Синдроме пацијената - Ni, Xiaohong; Wang, Jinhua; Tian, Yu; Ke, Hongyan; Liao, YuanGao; Lv, Yanwen (Journal of Medical Biochemistry, 2023)
Objective: The work was to analyze vasoactive and oxidative stress indicators for evaluating the efficacy of Continuous positive airway pressure (CPAP), and evaluate the relation of vasoactive and oxidative stress indicators and cardiac function in Obstructive Sleep Apnea Syndrome (OSAS) patients. Methods: OSAS patients (n = 120) from May 2021 to June 2022 were treated with CPAP. According to the clinical efficacy, the patients were divided into effective group and ineffective group. Vasoactive factors and oxidative stress indices were compared between the two groups to evaluate their clinical efficacy. The changes of cardiac function indices in the two groups were tested, and the correlation between vasoactive factors and oxidative stress indices and cardiac function was analyzed.Results: The effective rate of CPAP was 63.33% (76/120). Levels of Ang II, ET-1 and MDA were lower and SOD level was higher in the effective group than the ineffective group after treatment. AUC of the four indicators was all greater than 0.75. LPWT and IVST values of the effective group were lower than the ineffective group. A positive correlation was identified between the levels of AngⅡ, ET-1, and MDA with LPWT, between levels of ET-1 and MDA with IVST, and a negative correlation between SOD with LPWT and IVST.Conclusion: CPAP treatment can effectively improve the vascular activity and reduce the oxidative stress response of OSAS patients, and the combined detection of vasoactive factors and oxidative stress indicators is valuable for evaluating the efficacy of CPAP, and is related to cardiac function.